การศึกษาแนวทางการปรับปรุงห้องเรียนสถาปัตยกรรมภายในกรณีศึกษา : คณะสถาปัตยกรรมศาสตร์ผังเมืองและนฤมิตศิลป์, An Investigation of Renovation Design for Interior Learning Classroom, Case Study: Faculty of Architecture Urban Design and Creative art - โสภณพิศุตม์, กิ่งกาญจน์ (Asian Creative Architecture, Art and Design, 2018)
Abstract This research is the study of the renovation for AR-412-2 classroom, Faculty of Architecture Urban and Creative Arts Mahasarakham University by studying the current physical environment, the behaviors between the learner and the instructor in the activity area, and the problem of using interior space that directly affects to the learner. According to the survey, it was found that the area was not used as the expected purpose which is the specific learning classroom for interior architecture in addition with physical problems such as unfavorable areas, lack of equipment and lack of technology equipment and also lack of the friendly- learning environment. Data collections were conducted by the observation, questionnaire, interview and student assessment in the academic year 2016. The 100 samples were 1st- 5th year students in Interior Architecture classes, including teachers. To sum up, the appropriated classroom that response to activities and behaviors can motivate, encourage, enhance the learner learning skills, and beneficial to the instructor. The result shows that there are three design criteria 1) providing a variety of activities such as searching, learning, and meeting or group working and dividing an area for private uses including facilities, 2) designing an openplan layout to maximize visual interaction within the areas, 3) dividing an area into 2 zones, lecture area and group-working area. These areas should be divided with writable partition boards. In addition, design the classroom, it is suggested that materials for decorations, genius board, laptop, and internet system should be considered. Keywords : Learning Space Design, Post Occupied Evaluation, Interior Learning Classroom, Self-Directed Learning